1993
DOI: 10.1126/science.8235623
|View full text |Cite
|
Sign up to set email alerts
|

Rice Prolamine Protein Body Biogenesis: A BiP-Mediated Process

Abstract: Rice prolamines are sequestered within the endoplasmic reticulum (ER) lumen even though they lack a lumenal retention signal. Immunochemical and biochemical data show that BiP, a protein that binds lumenal polypeptides, is localized on the surface of the aggregated prolamine protein bodies (PBs). BiP also forms complexes with nascent chains of prolamines in polyribosomes and with free prolamines with distinct adenosine triphosphate sensitivities. Thus, BiP retains prolamines in the lumen by facilitating their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
131
0
1

Year Published

1995
1995
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(140 citation statements)
references
References 16 publications
8
131
0
1
Order By: Relevance
“…BiP has been shown to facilitate the folding and retention of the rice prolamin in the ER (Li et al, 1993a), and BiP has also been proposed to play a role in protein body biogenesis in the maize endosperm (Marocco et al, 1991;Zhang and Boston, 1992). Our data show that there is a higher accumulation of BiP in transgenic tobacco plants expressing the zein genes, suggesting that the presence of the zein protein in the ER triggers the induction of BiP.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…BiP has been shown to facilitate the folding and retention of the rice prolamin in the ER (Li et al, 1993a), and BiP has also been proposed to play a role in protein body biogenesis in the maize endosperm (Marocco et al, 1991;Zhang and Boston, 1992). Our data show that there is a higher accumulation of BiP in transgenic tobacco plants expressing the zein genes, suggesting that the presence of the zein protein in the ER triggers the induction of BiP.…”
Section: Discussionmentioning
confidence: 99%
“…Zeins do not possess the well-characterized KDEL ER retention motif (Pelham, 1990;Denecke et al, 1992); therefore, they must contain an as-yet-uncharacterized signal that is responsible for their retention in the ER. It has been suggested that prolamins are retained in the ER because of their interaction with an ERresident chaperone, such as BiP (Li et al, 1993a). BiP is a cognate of the 70-kD heat shock protein located in the Iumen of the ER; it has a C-terminal ER retention signal, and it functions as a chaperone (Haas and Wabl, 1983).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 OsBiP1 accumulates in a similar manner and is highly enriched at the periphery of PB-I through association with nascent prolamin polypeptide chains formed during translation; this indicates colocalization of OsERdj2 and OsBiP1. 6,31,32 OsERdj2 may be involved in translocation of prolamin polypeptides during PB-Iformation. This may be similar to the role of Sec63p in yeast, which, together with Kar2 (BiP), plays crucial roles in protein import into the ER.…”
Section: Erdj2mentioning
confidence: 99%
“…However, many of the seed proteins that accumulate in ER-derived protein bodies do not have the KDEL sequence. In the case of rice prolamines and corn zeins, it has been proposed that an ERresident chaperone, BiP, retains prolamines in the ER lumen by facilitating their folding and assembly into protein bodies Li et al, 1993b).…”
mentioning
confidence: 99%